EVIDENCE FROM CHARCOAL ANALYSIS FOR THE EXTENSIVE EXPLOITATION OF CORK-OAK (QUERCUS SUBER) FOREST IN THE ROMAN IMPERIAL PERIOD: THE VICUS OF THAMUSIDA (NW MOROCCO) - ALLEVATO, Emilia; PECCI, Alessandra; PAPI, Emanuele; Pasquale, Gaetano Di (Proceedings of the Fourth International Meeting of Anthracology, 2013)
This work shows the preliminary results of the study of charcoal collected in the vicus of Thamusida – Sidi Ali ben Ahmed (Morocco), in the Roman province of Mauretania Tingitana. The charcoal assemblage gives information on the woody flora and the wood usage during a period from the second half of the 1st cent. AD to the 3rd cent. AD, during the Roman occupation of the site. Data suggest the presence of a Quercus suber forest in the close surrounding of the site, with larger extension with respect to the present-day Mamora forest. The presence of Vitis vinifera and Olea europaea in the agrarian landscape was also detected. The presence within the charcoal assemblages of Castanea sativa it is worth to note since its presence in the wild vegetation in the surrounding of the site is rather improbable
The following values have no corresponding Zotero field: periodical: Proceedings of the Fourth International Meeting of Anthracology issue: September 2008
Keywords: CHARCOAL ANALYSIS; Firewood; Mamora forest; Roman imperial period; Timber

Modeling Multifunctional Agroforestry Systems with Environmental Values: Dehesa in Spain and Woodland Ranches in California - Campos, Pablo; Caparros, Alejandro; Cerdá, Emilio (Handbook Of Operations Research In Natural Resources, 2007)
The high environmental and amenity values of Mediterranean oak woodlands influence the response of the public and landowners to market forces and to public policies for the management of oak woodland areas. In California and in Spain, woodlands with a Quercus overstory open enough to allow the development of a significant grassy or shrubby understory harbor exceptional levels of biodiversity, provide watershed and habitat, sequester carbon, offer historically meaningful landscapes, and are pleasing to the eye. For historic reasons, and because of the social and environmental values of the woodlands for their owners, large private holdings based on sylvopastoral enterprises have and will have a crucial role in the future of the woodlands. Simple financial models for predicting landowner behavior based on response to market forces do not explain landowner retention of oaks without incorporation of landowner consumption of environmental and amenity values from the property, because landowner utility for oaks is not fully accounted for. By the same token, predicting the best afforestation approach considering carbon sequestration alone without consideration of the biodiversity and amenity values of native oaks risks an overvaluation of planting alien species that could have negative environmental and social consequences. Reforestation models for carbon sequestration that do not incorporate biodiversity and public amenity values might favor plantings of alien species such as eucalyptus; however, this does not take into account the high public and private consumption values of native oaks.
The following values have no corresponding Zotero field: periodical: Handbook Of Operations Research In Natural Resources electronic-resource-num: 10.1007/978-0-387-71815-6
Keywords: Carbon Sequestration; Firewood; Oak woodlands; Optimal Control; optimization model

Modeling Multifunctional Agroforestry Systems with Environmental Values: Dehesa in Spain and Woodland Ranches in California - Campos, Pablo; Caparros, Alejandro; Cerdá, Emilio (Handbook Of Operations Research In Natural Resources, 2007)
The high environmental and amenity values of Mediterranean oak woodlands influence the response of the public and landowners to market forces and to public policies for the management of oak woodland areas. In California and in Spain, woodlands with a Quercus overstory open enough to allow the development of a significant grassy or shrubby understory harbor exceptional levels of biodiversity, provide watershed and habitat, sequester carbon, offer historically meaningful landscapes, and are pleasing to the eye. For historic reasons, and because of the social and environmental values of the woodlands for their owners, large private holdings based on sylvopastoral enterprises have and will have a crucial role in the future of the woodlands. Simple financial models for predicting landowner behavior based on response to market forces do not explain landowner retention of oaks without incorporation of landowner consumption of environmental and amenity values from the property, because landowner utility for oaks is not fully accounted for. By the same token, predicting the best afforestation approach considering carbon sequestration alone without consideration of the biodiversity and amenity values of native oaks risks an overvaluation of planting alien species that could have negative environmental and social consequences. Reforestation models for carbon sequestration that do not incorporate biodiversity and public amenity values might favor plantings of alien species such as eucalyptus; however, this does not take into account the high public and private consumption values of native oaks.
Keywords: Carbon Sequestration; Firewood; Oak woodlands; Optimal Control; optimization model

Evaluation of the disposal of firewood of ilex pruning (Quercus ilex) in Andalusia and its characterization for the manufacture of wood cellulose pulp. - Gutierrez, J A; Alcaide, L J; Carmona, J A; Blanco, M J D; Ot, I P; Baldovin, F L (AFINIDAD, 2002)
In this work, it is analyzed the production of firewood of the ilex pruning in Andalusia, its real disposa and future forecast. Chemical characteristics are studied, in comparison with otherr wood species: Pine (Pinus pinaster) and Eucalyptus (Eucalyptus globulus), in order to obtain wood cellulosic pulp for paper. The average firewood production of the ilex pruning corresponding to 1975-78 in Andalusia was of 78.000 T/year, with a practically uniform trend. A statistical analysis with ARMA pattern let us estimate a yearly averge production of ilex pruning firewood around 72.500 T/year for the 1999-2006 period, which could have an upward correction if the exploitation in all hoamoak woods was total. For the manufacture of cellulosic pulp from ilex pruning wood, it would be necessary to separte the cortex due to a lower content of holocellulose and alpha-cellulose and a higher content of soluble substances and lignin. The content of lignin of ilex pruning wood is lower than the one of other wood species like Pinus Pinaster (76,7%), Eucalyptus globulus (56,4%) and olive grove pruning (8%).
Keywords: Firewood; forest residues; ilex; Quercus; Wood